THE EFFECT OF LEVERAGE, PROFIT MANAGEMENT AND CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE ON TAX AVOIDANCE - Ardan Gani Asalam; Hanif Al-Ghifari Ulwan Fakhri (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
Tax avoidance is a strategy or legal way carried out by companies by exploiting loopholes or weaknesses in the tax law itself. This research aims to re-examine whether leverage, earning management, and corporate social responsibility disclosure affect tax avoidance. The method used in this study is a quantitative method with a case study research strategy. This study used a purposive sampling technique which produced a sample of 22 out of 80 population of consumer goods industry companies listed on the Indonesia Stock Exchange for the 2019-2020 period. The results of the study found that simultaneously the variables leverage, earnings management, and corporate social responsibility affect tax avoidance. The results of the study also found that the leverage variable partially has a positive effect on tax avoidance, while the earnings management and corporate social responsibility variables partially do not affect tax avoidance.